2020
DOI: 10.22235/cp.v14i1.2179
|View full text |Cite
|
Sign up to set email alerts
|

Análisis psicométrico mediante la Teoría de la Respuesta al Ítem: modelización paso a paso de una Escala de Soledad

Abstract: La teoría de la respuesta al ítem (TRI) es un conjunto de modelos psicométricos utilizados en el desarrollo, evaluación, mejora y puntuación de escalas de evaluación. Este artículo pedagógico provee un recorrido inicial acerca de cómo conducir, interpretar y exponer resultados de aplicación de modelos de la TRI aptos para opciones de respuesta politómica ordenada. Los datos utilizados como ejemplo para la modelización con TRI corresponden a la administración de la Escala de Soledad de Buenos Aires, un nuevo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
3
1
2
Order By: Relevance
“…The findings of this study are also different from those of Suciati et al (2022), who reported that the PCM did not meet the model fit for the constructed-response test instrument they developed. The results of other studies are also inconsistent with ours, such as the study of Auné et al (2020), who reported that the GRM produced the best model fit parameters than the GRM, GPCM, and PCM. As a result, there has been no consistency in research results to determine the best polytomous scoring model up to this point.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are also different from those of Suciati et al (2022), who reported that the PCM did not meet the model fit for the constructed-response test instrument they developed. The results of other studies are also inconsistent with ours, such as the study of Auné et al (2020), who reported that the GRM produced the best model fit parameters than the GRM, GPCM, and PCM. As a result, there has been no consistency in research results to determine the best polytomous scoring model up to this point.…”
Section: Discussioncontrasting
confidence: 99%
“…For constructed-response (essay) items, the scoring used is polytomous. There are several mathematical models for polytomous scoring to choose from: graded response model (GRM), partial credit model (PCM), and generalized partial credit model (GPCM) (Auné et al, 2020;Hambleton et al, 1991;Retnawati, 2014;Yılmaz, 2019). The analysis using these three models has not been applied to the scoring and estimation of students' abilities in THE developed by the Open University.…”
Section: Introductionmentioning
confidence: 99%
“…The various examples of the marital quality instruments show that reliability is the focus of psychometric property analysis. Whereas reliability estimated using the Classical Test Theory approach (e.g., Cronbach Alpha) found weaknesses that depend on the particular samples of individuals who responded to the instrument (Auné et al, 2020;Rusch et al, 2017) coefficient of a measuring instrument only applies to the research sample because it depends on the data sample. The magnitude of the coefficient will be different in other research samples, so the reliability coefficient will always be estimated for each research data, even though the instrument is the same.…”
Section: Introductionmentioning
confidence: 99%
“…If the response is dichotomous, the models are one logistic parameter (1-PLM), two logistic parameters (2-PLM), or three logistic parameters (3-PLM). If the response categories are more than two, the polytomous IRT is the most suitable model (Auné et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Di Indonesia, penelitian yang menggali karakteristik psikometrik tes uraian Kimia Dasar I menggunakan Andrich RSM cukup sulit ditemukan, umumnya karakteristik hanya dieksplorasi menggunakan Teori Tes Klasik. Padahal sudah jelas Teori Tes Klasik memiliki berbagai kelemahan dan sudah mulai ditinggalkan (Auné, Abal, & Attorresi, 2020). Untuk itu, penelitian ini dilakukan untuk mendeskripsikan psikometrik dari instrumen tes uraian Kimia Dasar I menggunakan Andrich Rating Scale Model.…”
unclassified